Partisipasi Anggota Kelompok Tani dalam Pengembangan Usahatani Hortikultura di Kecamatan Pacet Kabupaten Cianjur - Fita Dwi Untari; Dwi Sadono; Lukman Effendy (Jurnal Penyuluhan, 2022)
The horticultural sub-sector has the prospect of boosting the economic value and income of farmers. This study aims: (1) to analyze perception of farmer group members about the role of the group in the development of horticultural farming and the factors that influence; (2) to analyze participation of group members in the development of horticultural farming and the factors that influence; and (3) developing strategies to increase group member participation. This study used a survey method and was conducted from February to April 2021 in Pacet District, Cianjur Regency, West Java Province. The samples this study were 100 people. The analysis method used was descriptive and inferential statistics (Path Analysis) equipped with qualitative data. The results showed: (1) perception of farmer group members was in the medium category, influenced by extension activities; (2) participation of group members was in the medium category, directly influenced by members' perceptions of the role of farmer groups, access to information, the length of formal education, and negatively affacted by involvement on group; (3) Strategies to increase participation are through efforts: enhancement the role of farmer groups, utilization of access to information, optimizing the role of change agents, and enhancement quality of extension services.